New records of the squat lobster genus Uroptychus (Crustacea: Decapoda: Anomura: Chirostylidae) from West Africa: unexpected occurrence of the western Atlantic species U. nitidus (A. Milne Edwards, 1880) and description of a new species - Baba, Keiji; Macpherson, Enrique; Rodríguez-Flores, Paula C. (Zootaxa, 2025)
Collections of a recent expedition to Guinea-Bissau, West Africa conducted by the Spanish Institute of Oceanography contain five specimens of two unusual species of the squat lobster genus Uroptychus Henderson, 1888, taken at 909 m depth. One of these represents an unidentified species herein described as U. pauroptilus sp. nov. and the other four are referable to U. nitidus (A. Milne Edwards, 1880), so far known only from the western Atlantic. The morphological relationships between the new species and its close relatives U. maroccanus Türkay, 1976 and U. tuerkayi Baba & Macpherson, 2017, both from the eastern Atlantic, are discussed. The identity of U. nitidus was confirmed by morphological and molecular analyses of a large series of specimens from the western and eastern Atlantic and by comparison with material of U. concolor (A. Milne-Edwards & Bouvier, 1894) from the eastern Atlantic. Phylogenetic relationships of these species as well as additional comparable species are discussed.